Cyber operations and the use of force in international law - Roscini, Marco (Oxford University Press, 2014)
Recent years have seen a significant increase in the scale and sophistication of cyber attacks employed by, or against, states and non-state actors. This book investigates the international legal regime that applies to such attacks, and investigates how far the traditional rules of international humanitarian law can be used in these situations